Examining Quality of Life After Treatment with Azelaic and Pyruvic Acid Peels in Women with Acne Vulgaris - Chilicka K; Rogowska AM; Szyguła R; Taradaj J (Dove Medical Press, 2020)
Karolina Chilicka, 1 Aleksandra M Rogowska, 2 Renata Szyguła, 1 Jakub Taradaj 3 1Faculty of Health Sciences, University of Opole, Opole, Poland; 2Institute of Psychology, University of Opole, Opole, Poland; 3Institute of Physiotherapy and Health Sciences, Academy of Physical Education, Katowice, PolandCorrespondence: Karolina ChilickaFaculty of Health Sciences, University of Opole, Opole 45-060, PolandEmail karolina.chilicka@poczta.onet.plPurpose: This randomized parallel study aims to investigate the azelaic acid (AA), and pyruvic acid (PA) peels treatment effect on health-related quality of life (QOL) in young adult women with acne vulgaris.Patients and Methods: The participants were 120 female undergraduate students, with mild to moderate facial acne and an average age of 22 years old (M = 22.2, SD = 16.1). Eligibility criteria were as follows: female gender, 18– 25 years of age, no dermatological treatment within the last 12 months and mild to moderate papulopustular acne. Patients were randomly divided into two groups, the first group was treated with AA, and the second group was treated with PA. Both groups received treatment every 2 weeks, for a total of 12 weeks. The Hellgren–Vincent scale was used to assess acne severity, and the Dermatology Life Quality Index (DLQI) and Skindex-29 were used to evaluate the quality of life of each patient. These scores were calculated before treatment, and after finishing the final treatment.Results: All scoring systems used (Hellgren–Vincent scale, DLQI, and Skindex-29) demonstrated improvement in both groups. QOL scores were slightly better in the group using pyruvic acid compared with azelaic acid.Conclusion: Both AA and PA have a significant impact on the objective assessment of acne symptoms, as well as the subjectively measured quality of life of young adult women with acne. There is a slightly greater improvement in QOL scores with PA compared with AA peeling treatment.Keywords: azelaic acid, acid peels, DLQI, pyruvic acid, Skindex-29, women